Importance of efficient managent of the operating cycle in SMEs - Bermúdez Carrillo, Luis Alberto (2026)
This study analyzes the importance of efficient management of the operating cycle by SMEs as a strategy to achieve operability, competitiveness, and its permanence over time. Proper management of the operating cycle allows you to have enough information to estimate and cover your cash needs, and the limits you must manage credit or cash operations. To carry out this, a bibliographic review was made in the first instance to theoretically support the elements of both the operating cycle and the cash conversion cycle. Subsequently, a survey was applied that allowed to argue the need, the degree of knowledge and application of the operating cycle and the data that allow knowing the number of days in which these SMEs operate. As a result, it was determined that a considerable number of SMEs are unaware of the management of the operating cycle, therefore, they do not incorporate this information in decision-making. Regarding the management of the collection, payment and inventory cycles, the results found are contrary to what is applied in good administrative practice, and to what the theory indicates. On the other hand, although they are clear about the number of days they spend collecting and paying, they do not have training that allows them to realize what the implications of current cycles are. This application refers to the financial impact they have due to the fact of operating with ignorance and empirically.